2018
DOI: 10.1021/acsami.8b04289
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Magnetism in Graphene Induced by Proximity to EuO

Abstract: Addition of magnetism to spectacular properties of graphene may lead to novel topological states and design of spin logic devices enjoying low power consumption. A significant progress is made in defect-induced magnetism in graphene-selective elimination of p orbitals (by vacancies or adatoms) at triangular sublattices tailors graphene magnetism. Proximity to a magnetic insulator is a less invasive way, which is being actively explored now. Integration of graphene with the ferromagnetic semiconductor EuO has m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 51 publications
0
51
0
1
Order By: Relevance
“…Poor magnetic properties are improved by proximity interaction in 2D carbons by the interaction of magnetic insulators like europium chalcogenides (EuO), yttrium iron garnet (YIG), etc. [133][134][135] Recently, Averyanov et al 136 have shown experimental evidence of high-temperature magnetism in graphene induced by proximity to EuO, a salient magnetic semiconductor. Fig.…”
Section: Magnetism Induced By the Proximity Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor magnetic properties are improved by proximity interaction in 2D carbons by the interaction of magnetic insulators like europium chalcogenides (EuO), yttrium iron garnet (YIG), etc. [133][134][135] Recently, Averyanov et al 136 have shown experimental evidence of high-temperature magnetism in graphene induced by proximity to EuO, a salient magnetic semiconductor. Fig.…”
Section: Magnetism Induced By the Proximity Effectmentioning
confidence: 99%
“…The inset plot indicates the T dependence of the AHE resistance (at À9 T, saturated state) in the EuO/graphene structure, reproduced with permission from ref. 136, copyright 2018, American Chemical Society. Thus, the gate voltage helps to adjust the E F to fulll the Stoner criterion (IN(E f ) > 1, where N(E f ) are the DOS at E F in the nonmagnetic case, and I is the Stoner parameter).…”
Section: Gate Voltage (V G )-Tunable Magnetismmentioning
confidence: 99%
“…While the europium trioxide (Eu 2 O 3 ) is a wide band gap oxide relevant mainly for lighting applications, such as sensitization in lanthanide-doped inorganic nanocrystals, 7 additive-free red-emitting transparent ceramics, 8 high quantum efficiency phosphors, 9 dense translucent ceramics, 10 and much more, the europium monoxide (EuO) is a ferromagnetic semiconductor 11 showing interesting magnetic properties, becoming ferromagnetic below a Curie temperature at 69 K. 12 Recently, for example, inducing magnetism by proximity in two-dimensional materials such as graphene has been reported. 13 Moreover, europium monoxide belongs to a compact group of magnetic semiconductors (europium chalcogenides) with unique electronic, magnetic, optical, and magneto-optical (MO) properties. 14 For applications in optoelectronics, it is particularly significant that the band gap of EuO at room temperature is 1.12 eV, which is comparable to that of silicon, which would allow spin-polarized electronic injection.…”
Section: Introductionmentioning
confidence: 99%
“…where χ=±1 is the chirality, v is the Dirac velocity of electrons, and Δ is the energy difference between A and B sublattice sites. This system can be found in graphene or other honeycomb monolayers on top of magnetic substrates such as yttrium iron garnet [21,22] or EuO [23]. Since TRS is broken, we will focus on just a single cone.…”
mentioning
confidence: 99%
“…In summary, we demonstrate how fast pseudo-spin dynamics can be tracked through a pulsed non-adiabatic excitation, manifesting in ACM without magnetic field. ACM can be found in a variety of anomalous Hall materials for example intrinsic anomalous Hall systems in magnetic materials [25], ferromagnetic insulators: Cr-Ge-Te alloy films [26], CoFe 2 O 4 [27], EuO [28]; dilute magnetic semiconductors: (Ga, Mn)As [29]; magnetically doped topological insulators: Cr doped (Bi, Sb) 2 Te 3 [30], gapped 2D Dirac materials (graphene, silicene, germanene, and transition metal dichalcogenides) on top of magnetic substrates [21][22][23], and broken TRS 3D Dirac and Weyl semimetals. ACM displays a number of unusual characteristics including an intrinsic power-law decay, and real-space charge displacements that follow a spiral-like trajectory.…”
mentioning
confidence: 99%